Generalized Cost-Effectiveness of Residential Wind Mitigation Strategies for Wood-Frame, Single Family House in the USA - Orooji, Fatemeh; Friedland, Carol J.; Savio, Rose Dominic; Taghinezhad, Arash; Massarra, Carol C.; Bushra, Nazla; Rohli, Robert V. (Frontiers in Built Environment, 2022)
Wind is one of the deadliest and most expensive hazards in the United States. Wind hazards cause significant damage to buildings and economic losses to homeowners. Economic losses average approximately $3.8 billion annually from hurricane winds and are not decreasing, even despite enhanced construction practices to reduce wind damage. Thus, the effectiveness of mitigation strategies should be evaluated in order to lower the cost incurred by this hazard. Several studies have suggested building code improvements to mitigate the wind hazard, this additional comprehensive research provides selecting economically beneficial mitigation strategies to consider in building code revisions. In a step toward addressing this need, the current study was conducted to determine the cost effectiveness of mitigation strategies for new and retrofit construction of a wood-framed, single-family, residential building case study. Net benefit, defined as the difference between the life-cycle wind loss before and after implementation of the mitigation strategy, was calculated for 15 wind mitigation strategies and their combinations, with new and retrofit construction costs ranging between $1,200 to $12,000 and a decision-making time horizon ranging between 5 and 30 years. Payback periods, defined as the number of years to recover the investment, were calculated for each mitigation strategy. Results were summarized by cost effectiveness for all ASCE 7 wind speed contour intervals. The results of this study serve as a starting point for further refinement of the economic justification needed to properly evaluate potential building code changes.